Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1159/000477247
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Vegetarianism and Seasonal Affective Disorder? A Pilot Study

Abstract: Background and Aim: Seasonal patterns of food intake are found in healthy individuals and particularly in patients with seasonal affective disorder (SAD). One nutritional choice is a vegetarian diet. Methods: In a Finnish population study, FINRISK 2012, information about diet and SAD was collected. In a Dutch outpatient clinic, SAD patients were asked if they were vegetarian. Results: The percentage of SAD patients among Finnish vegetarians was 4 times higher than in the normal population. The percentage of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Among them, studies were excluded for not focusing on SAD ( n = 12), including subjects with other major depression as comparisons ( n = 1), outcomes unrelated to our objective ( n = 3), being review articles ( n = 2), the full text not being available ( n = 1), supplementation being given not through oral administration ( n = 2), not involving dietary intervention ( n = 5), and not using a validated tool for SAD screening ( n = 2). In total, we included data from 11 studies in the current systematic review (Krauchi and Wirz-Justice, 1988 ; Rosenthal et al, 1989 ; Berman et al, 1993 ; Oren et al, 1994 ; Krauchi et al, 1997 ; Danilenko et al, 2008 ; Mischoulon et al, 2010 ; Donofry et al, 2014 ; Frandsen et al, 2014 ; Meesters et al, 2016 ; Morales-Munoz et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among them, studies were excluded for not focusing on SAD ( n = 12), including subjects with other major depression as comparisons ( n = 1), outcomes unrelated to our objective ( n = 3), being review articles ( n = 2), the full text not being available ( n = 1), supplementation being given not through oral administration ( n = 2), not involving dietary intervention ( n = 5), and not using a validated tool for SAD screening ( n = 2). In total, we included data from 11 studies in the current systematic review (Krauchi and Wirz-Justice, 1988 ; Rosenthal et al, 1989 ; Berman et al, 1993 ; Oren et al, 1994 ; Krauchi et al, 1997 ; Danilenko et al, 2008 ; Mischoulon et al, 2010 ; Donofry et al, 2014 ; Frandsen et al, 2014 ; Meesters et al, 2016 ; Morales-Munoz et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…One cross-sectional study investigated the possible link between vegetarianism and SAD (Meesters et al, 2016 ). By using available data from the Finnish national FINRISK 2012 study and data from the outpatient clinic for SAD in the Netherlands, the author of that study found an association between being vegetarian and SAD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations